Design and synthesis of leucylaniline derivatives as leucyl-tRNA synthetase inhibitors. (9th February 2022) - Luo, Jinghan; Wu, Chengjun; Hu, Yanjun; Jia, Xingxing; Chen, Yu; Sun, Tiemin
Abstract : By simulating the structure of Leu-AMP, 26 leu-arylamine derivatives were designed and synthesized as leucyl-tRNA Synthetase inhibitors; compounds 19 and 24 showed good anti-tuberculosis activity. Abstract : By simulating the structure of Leu-AMP, an intermediate of tRNA synthesis, 26 leu-arylamine derivatives were designed and synthesized by retaining leucine and replacing adenosine phosphate with amido-substituted aniline. All compounds were designed under the guidance of computer aided drug design, and their drug-like properties were fully considered. The inhibitory activities of all compounds against LeuRS inhibitory enzymes and Mycobacterium phlei 1180 were tested. Most of the compounds show inhibitory activity against LeuRS inhibitory enzymes and Mycobacterium phlei 1180 . Six compounds (18, 19, 20, 21, 24 and 25 ) were screened using Mycobacterium tuberculosis H37Ra . These compounds have a strong inhibitory effect on Mycobacterium tuberculosis H37Ra . Molecular docking research also shows the same results, which fully verifies the design idea. We also found that the existence of hydrogen bond acceptors on the compounds leads to strong hydrogen bonds with the key amino acids of proteins.